Statistical Studies on Family Budgets of Population of USSR: Problem of Reliability (on Materials of State Archive of Sverdlovsk Region) - V. N. Mamyachenkov (Научный диалог, 2017)
The study focuses on a very important historiographical and methodological problem, because the accuracy of the source base and scientific literature has always been a cornerstone issue in the course of historical research of any scale. The relevance of the subject is determined by its high significance to the social sciences, primarily economics, history and political science. It is argued that the materials of the statistical surveys of family budgets of the population represent a unique source of information. It is stated that the data of budget surveys impartially indicate the true level of income, expenditure and consumption of the population, giving scientists the opportunity to reconstruct an objective picture of our past, free from ideological blinders and propaganda clichés. It is proved that some errors and inaccuracies found in the materials of budget surveys in no way can affect a very positive assessment of their reliability. It is emphasized that these materials had not originally intended for wide publicity and discussion, which makes unlikely their deep and deliberate falsification as a systematic phenomenon. Scientific novelty of the work lies in the fact that it systematizes, generalizes and presents exclusive material pertaining to budget research on the example of Sverdlovsk region.